An investigation of the physiological and biochemical responses elicited by Panulirus cygnus to harvesting, holding and live transport. - Spanoghe, Patrick T. (Curtin University, 1996)
The western rock lobster (WRL), Panulirus cygnus is a decapod crustacean which is found in abundance in the coastal waters of Western Australia and which supports a major fishery of economic importance for the State, with an annual harvest ranging between 10-12 million kilograms. The growth of the existing markets in Asia for live exports and the competition exerted by other countries marketing spiny lobsters prompted the need for the Industry to assess and develop post-harvest handling procedures likely to contribute to an improved quality of live product. The physiological responses of P. cygnus to handling and transportation were virtually unexplored.The objectives of this project were, (i) to generate information with regard to the biological phenomena underlying morbidity and mortality of lobsters during live export shipments, (ii) to investigate the physiological responses of P. cygnus to the post-harvest handling practices currently used by the WRL industry in their five export program and, (iii) to identify protocols by which post-harvest handling techniques could be modified to reduce the occurrence of morbidity and mortality during five export.These objectives were achieved through, (i) a field survey conducted during the course of the 1992/93 fishing season, investigating the relative influence of environmental factors and processing techniques on the incidence of lobster morbidity+mortality during simulated live shipments and, (ii) a series of field experiments that monitored the physiological responses elicited by lobsters to post-harvest handling procedures and simulated live shipment conditions.From the field survey, it appeared that the rate of morbidity+mortality experienced in simulated live shipments, within the three processing units surveyed, averaged 5.22 +/- 0.63 %, with a highly significant difference (p [less than] 0.001) between the processing units. Scrutiny of the data revealed a major influence of two factors directly related to post-harvest handling procedures: a) the time spent under normal commercial conditions in packaging export cartons and, b) the ambient temperature within the export cartons. Following 30-36 hrs in packaging, the percent mortality increased twofold, from 5.2 +/- 0.0 % recorded following 20 - 24 hrs to 10.4 +/- 2.3%. With regard to the ambient temperature within the export carton, temperatures between 17.5 and 20.0 degrees celsius appear to be optimal for P. cygnus survival while temperatures above 20.0 degrees celsius induce significantly greater morbidity and mortality.A number of factors were identified as having a potential influence on lobster physiological responses to post-harvest handling conditions:a)Immediately after harvesting, lobsters are subjected to a range of transport environment options, according to their origins: i.e., (i) direct delivery from fishing vessels by local fishermen to the processing facility, (ii) onshore transportation by truck from coastal depots and, (iii) transport in baskets on board carrier-boats from the Houtman Abrolhos Islands.b) After delivery, lobsters are subjected to sorting and grading procedures, with a concomitant exposure to air and disturbance.c) Recovery in holding tanks is usually allowed for a period ranging between 24 to 72 hours.d) Prior to being packed in export cartons, lobsters are subjected to a short period (30 sec to 3 min) of immersion in chilled water (8 - 12 degrees celsius), the procedure varying from one processor to the other.e) During subsequent periods of transit in export cartons, (up to 48 hrs) lobsters are subjected to aerial exposure and fluctuating ambient temperature.A comparison of the physiological profiles of lobsters from different origins revealed significant differences, with respect to a range of physiological variables. On the basis of visual estimates of health status, lobsters from the "local" origin exhibited a consistently superior condition, when compared to "coastal" and "carrier-boat" animals. The examination of physiological variables revealed consistent trends reflecting the visual assessments. "Local" lobsters exhibited significantly lower levels in anaerobic metabolic waste concentrations, with the haemolymph lactate titre between 2.77 +/- 0.19 and 4.33 +/- 0.56 mmol L(subscript)-1, compared with the other groups, between 5.23 +/- 0.24 and 8.86 +/- 1.29 mmol L(subscript)-1. A 250 to 300% increase in haemolymph ammonia concentration was observed between "coastal" and "carrier-boat" groups and the "local" lobsters, at 0.32 +/- 0.02 mmol L(subscript)-1. Significantly higher pH values were recorded for the "local" group, at 7.72 +/- 0.04, compared with values below 7.64 +/- 0.04 for the other groups. "Local" lobsters recorded 8 to 15 times less circulating glucose, at 0.11 +/- 0.03 mmol L(subscript)-1, having 50% more ATP in their muscle tissues, at 6.07 +/- 0.15 mu mol g(subscript)-1 and 250% more arginine phosphate, at 6.56 +/- 0.72 mu mol g(subscript)-1.An assessment of the efficiency of the industry sorting procedures revealed differences between selected and rejected animals with regard to the ATP and arginine phosphate concentrations in their muscle tissues with, as a common trend for both variables, selected animals recorded higher values. Significant differences were identified within the "local" group of lobsters, with selected animals recording 40% more ATP, at 6.92 +/- 0.63 mu mol g(subscript)-1 and 30 % more arginine phosphate, at 7.77 +/- 1.01 mu mol g(subscript)-1.A monitoring of the physiological profiles of lobsters subjected to extended (up to 8 hours) periods of onshore transportation in trucks revealed a significant reduction in their health status. A consistent and almost linear fall in the concentration of total adenylate (35%), to 5.46 +/- 0.50 mu mol g(subscript)-1 and phosphagen reserve (70%),to 2.77 +/- 0.26 mu mol g(subscript)-1, were recorded throughout the 8 hour period. For up to 6 hours the concentration of lactate in the leg muscle tissues increased by 0.95 mu mol g(subscript)-1 h(subscript)-1 and then by 4.7 mu mol g(subscript)-1 h(subscript)-1,to reach 20.57 +/- 1.61 mu mol g(subscript)-1 after 8 hours. Haemolymph glucose and ammonia titres recorded a 3.5 fold increase over the first 6 hours, to reach 2.14 +/- 0.54 and 1.17 +/- 0.16 mmol L(subscript)-1, respectively, the last period (6 to 8 hours) being characterised by a 1.6 and 1.9 fold decrease in concentration. Lobsters were able to maintain their haemolymph pH close to 7.77 during the first four hours, with a concomitant rise in haemolymph calcium concentration. From the results, it appeared that, under current industry procedures, extending the period during which lobsters are transported in spray trucks to more than 6 hours is conducive of altered physiological status.An assessment of the effects of short periods (up to 60 min) of aerial exposure and disturbance revealed significant changes in the physiological profiles of lobsters. When exposed to air, lobsters exhibited a significant fall in haemolymph pH, a rise in lactate concentration, and a depletion in energy reserves. Lobsters left undisturbed were able to buffer an incipient acidosis for up to 40 min (7.78 +/- 0.03), after which a decline in pH was recorded to reach 7.71 +/- 0.02. Conversely, disturbed animals experienced an uncompensated acidosis and a decrease by 0.7 of a unit over a 60 minute period. Similarly, undisturbed lobsters did not demonstrate behavioural signs of stress while disturbed animals exhibited dramatically diminished responses to handling after 60 min of exposure. Both disturbed and undisturbed animals recorded a decline in ATP/ADP, to reach after 40 min, 8.31 +/- 0.77 and 5.05 +/- 0.45, respectively, compared to 13.18 +/- 1.69 (control). During the last period (40 to 60 min), the undisturbed animals recorded a 40 % decrease in ATP concentration, to reach 4.42 +/- 0.16 mu mol g(subscript)-1, while a 53% decline was recorded in the disturbed group, to 3.59 +/- 0.41 mu mol g(subscript)-1. During aerial exposure, the phosphagen reserve recorded a 55% decrease in the disturbed animals, at 4.82 +/- 1.37 mu mol g(subscript)-1, compared to 20% in the undisturbed group, at 8.64 +/- 0.87 mu mol g(subscript)-1. A 100% increase in lactate ion concentration was recorded in the muscle tissues of disturbed animals to reach 5.53 +/- 0.49 mu mol g(subscript)-1, compared to a 15% increase in the undisturbed group, at 2.83 +/- 0.29 mu mol g(subscript)-1.The monitoring of the physiological profiles of lobsters during extended periods (up to 72 hrs) of recovery in holding tanks revealed significant shifts in their physiological profiles and that a return to a steady state occurred only after 8 to 48 hours following re-immersion, according to the environmental conditions and the origin of the animals. Resting levels were identified after 24 hours for the haemolymph pH (close to 8.00), for the concentration in lactate, ions in the muscle tissues (2.00 to 3.00 mu mol g(subscript)-1 for the haemolymph glucose titre (0.30 to 0.60 mmol L(subscript)-1), for the haemolymph ammonia titre (close to 0.25 mmol L(subscript)-1), for ATP (6.50 to 7.70 mu mol g(subscript)-1), and for the phosphagen reserve (12.2 to 16.70 mu mol g(subscript)-1). Longer periods ([greater than]/= 48 hrs) were required for full recovery to occur when lobsters were stored at high stocking density and when lobsters were not isolated from their artificial environment. Extending the recovery period to 72 hrs resulted in slight changes in the physiological profiles of lobsters, with a 20 % decline in ATP/ADP, a 10% decrease in phosphagen concentration in the muscle tissues of the lobsters and subdued behavioural responses for those lobsters held at higher stocking densities.No attempt was made in the present study to establish the resting levels for the physiological variables surveyed. In a number of experiments, "control" groups have been studied and used as reference points to monitor changes accompanying exposure to a range of environmental conditions. The data pertaining to these different groups revealed a variability for most of the variables surveyed, suggesting that it would be hazardous to assume that these animals were undisturbed and to state with confidence that the values recorded for the variables surveyed would represent resting levels.The physiological responses of lobsters subjected to chilling procedures was investigated and significant physiological changes were identified. Short chilling procedures (3 and 6 min) were conducive of a dramatic reduction of the behavioural responses to handling, a reduction in pH values ranging between 0.13 and 0.24 of a unit, a rise in haemolymph lactate concentration by 1 to 2.6 mmol L(subscript)-1, a 20 to 100% increase in haemolymph glucose titre, a 35 to 75% decrease in phosphagen concentration. Extending the chilling period for up to 24 hrs resulted in a progressive return to control levels for most of the physiological variables surveyed. However, physiological signs of disturbance remained perceptible between 2 to 15 hours, as demonstrated by elevated lactate concentrations, lowered ATP and AP concentrations and lowered ATP/ADP values.Lobster body core temperature (CBT) reduction resulting from immersion in chilled water suggested that limited cooling effects were achieved by using the standard chilling procedures currently used by the WRL industry. Using "A" size lobsters (395 - 453 gr), a reduction of the CBT by 0.5 to 0.8 degrees celsius was recorded after 1 and 3 min immersion in 12 degrees celsius water, highlighting the limited low temperature effect exerted by these procedures in lowering the overall temperature of the mass of the product to be packed into export cartons.A study of the general physiological responses of lobsters to simulated live transport conditions in export cartons was conducted, investigating the effects of the period spent by the animals in export cartons, the effects of environmental temperature and the impact of chilling regimes. No attempt was made to duplicate exactly the conditions of cartons shipped overseas, that is carted by trucks to the airport and then transported by air to foreign markets. This study revealed that during the first 4 hours of transit, the animals exhibited physiological changes probably related to delayed responses to handling, disturbance and chilling procedures, as demonstrated by a decline in pH (0.1 to 0.3 of a unit), a rise in haemolymph ammonia (0.5 to 1 mmol L(subscript)-1) and glucose (0.5 mmol L(subscript)-1) titres, an increase in muscle lactate concentration (0.5 to 1 mu mol g(subscript)-1, a decrease in ATP concentration (1.5 mu mol g(subscript)-1, and a partial replenishment of the phosphagen reserve. These changes were less pronounced for those lobsters which underwent intermediate (30 min) chilling treatments.The subsequent periods (to 48 hours) were characterised, for all the treatments, by a rise in lactate concentration in the muscle tissues, this response being delayed for those lobsters which underwent a "6 min" or "30 min" chilling treatment. The data suggested that moderate changes in haemolymph lactate titre resulted from the increase in muscle lactate concentration, up to values ranging between 6 and 8 mu mol g(subscript)-1, beyond which levels, haemolymph lactate rose dramatically, to reach values up to 19.98 mmol L(subscript)-1. The ATP concentration remained relatively constant up to 18 - 26 hours, after which a steep decline was recorded to reach values below or close to 4 mu mol g(subscript)-1 after 42 hours, suggesting that the adenylate pool was maintained, probably through aerobic and anaerobic pathways of energy generation and by the "buffering" role played by the phosphagen reserve. After 24 to 36 hours, all the lobsters exhibited signs of energy depletion, as demonstrated by the changes in ATP/ADP ratio. A concomitant increase in lactate ion concentration and a decrease in haemolymph glucose titre was recorded, suggesting that anaerobic metabolism had become the major component of energy production. Simultaneously, a marked increase in the internal carton temperature was identified, which probably induced an increase in the metabolic rate of the lobsters. This "temperature effect" was delayed for up to 32-38 hrs transit, for those lobsters which underwent intermediate (30 min) and extended (24 hrs) chilling treatments. The changes in haemolymph pH and calcium titre suggest that the initial decline in pH identified at the completion of the first 4 hours of transit was, at least partially, compensated after 26 - 32 hours. A 30 to 40% increase in haemolymph calcium titre was recorded after 4 hours of transit, suggesting that bicarbonate ions were released in order to buffer the pH of the haemolymph. However, a decrease in pH (0.1 to 0.3 of a unit) was recorded during the subsequent periods suggesting that the bicarbonate buffering capacity did not suffice to match the recorded massive rise in lactate titre.By extending the duration of the chilling procedures and by using refrigerated material (wood-shaving fillers, ice-bottles), lower temperatures were achieved inside the packaging cartons and these were maintained for longer periods of transit (up to 20 hours), delaying the effect of the external environment on the temperature changes recorded inside the cartons and the concomitant metabolic responses of the animals. This effect was also achieved by maintaining the cartons in controlled temperature environments ([less than] 20 degrees celsius) and, to a lesser extent, by improving the insulation capacity of the polystyrene cartons.This study constitutes an overview of the physiological responses of Panulirus cygnus to post-harvest handling procedures currently used by the WRL industry. It revealed that an improved return for the Industry could be achieved by reducing the debilitating effects exerted on the lobsters by handling, exposure to air and elevated environmental temperature. It provides direction for future research, aimed at improving the quality and hence, the financial return in the live export of WRL.